TRICHODERMA SPP: MULTIFACETED MECHANISMS OF BIOCONTROL AND PLANT GROWTH PROMOTION (International Journal of Food and Nutritional Sciences, 2023)
Recent shift in trends of agricultural practices from application of synthetic fertilizers and pesticides to organic farming has brought into focus the use of microorganisms those carryout analogous functions. Exploitation of agriculturally important microorganisms in plant growth promotion and antagonistic potential is a well investigated area. Trichoderma spp. are widely acknowledged for their potential to parasitize plant pathogenic fungi and have been efficiently utilized for biocontrol of wide range of seed and soil borne phytopathogens.